Integrated silicon-based spectral reshaping intermediate structures for high performance solar thermophotovoltaics. (1st January 2023) - Hou, Guozhi; Lin, Zhenhui; Wang, Qingyuan; Zhu, Yu; Xu, Jun; Chen, Kunji
Graphical abstract: Highlights: The spectral reshaping intermediate structure on silicon substrate with simple fabrication process. The hierarchical Si NW absorber exhibits an excellent optical absorption performance from 220 nm to 1100 nm and a lower emittance above 1100 nm. The Si-W-SiN/SiNO multilayer emitter shows a selective narrowband absorption (i.e., emission) peak in the target wavelength and low thermal radiation loss in long wave range. The overall efficiency of the whole STPV system is precisely optimized by varying emitter parameters and system parameters. At achievable light concentration intensity of 1000, the STPV system efficiency can exceed 29% using this integrated silicon-based intermediate structure. Abstract: Solar thermophotovoltaics (STPV) system is a technique that uses absorber and emitter to remold wide-band solar radiation into narrowband infrared emission and then convert it into electric energy in order to get high energy conversion efficiency. In this study, we fabricated an integrated silicon-based intermediate structure to enable the spectral reshaping. The absorber is a hierarchical Si NW structure, which exhibits excellent absorption performance of over 95 % in the spectral range of 220–1100 nm and a low heat loss in the long-wavelength band. The emitter is planar Si-W-SiN/SiNO structure, exhibiting a selective narrowband absorption (i.e., emission) peak in the target wavelength. When the emission peak of emitter is at 1800 nm, the overall efficiency of the STPV system based on this silicon-based intermediate structure can theoretically exceed 29 % with an achievable solar concentration of 1000 and an emitter-to-absorber area ratio of 4. We also test the prepared spectral reshaping intermediate structures on real systems and discuss further optimizations.